EFFECTIVENESS OF PROPRIOCEPTIVE RE-EDUCATION AGAINST STRENGHT & STRETCH ON BALANCE, GAIT, QUALITY OF LIFE AND FALLS IN THE ELDERLY (Cuestiones de Fisioterapia, 2011)
Introduction: falls, balance and gait difficulties are common in aged and laid into mobility and mortality. Many studies evaluated the effects of physical therapy but there is not conclusive evidence of which physical intervention is more appropriate. Objectives: a) To compare the effectiveness of a proprioception reeducation programmed against a stretch & strength exercise programmed for gait and balance in elderly community. b) To find out any relationship between gait and balance improvement and reduction in number of falls and better quality of life. Subjects and methods: a randomized single-blinded pilot clinical trial is performed. Elderly from Casco Antiguo Geriatric in San Fernando de Henares (n = 24) accomplishing inclusion criteria (no neurological/ cognitive impairment and conser-ving gait) were selected. Subjects under 65 were excluded. Elderly were randomly allocated into two groups. Group 1 received 14 proprioception re-education sessions. Group 2 underwent 14 stretch&strength sessions. Assessments were gait speed; balance by one-leg stand test; quality of life by SF-36 and fall rate. Follow up was post-interven-tion. Results: preliminary results do not show significant differences between groups. Gait speed improved in group 1 (p=0.033), where significant correlations were found between balance and gait (p = 0.020) and physical (p = 0.050) and mental (p = 0.039) domains of SF-36. In group 2, a significant correlation between gait and physical domain of SF-36 (p = 0.013) was found. Conclusions: there are not differences between groups. Proprioceptive reeducation is effective to improve gait and stretch & strength is more linked to quality of life.